Sakinah Pedagogy: Challenges of Implementation in the Malaysian Education System - Che Noh, Mohd Aderi; Ahmad, Aliza Che; Zainur, Elhaq (Jurnal Pendidikan Nusantara, 2024)
This study explores the challenges of implementing Sakinah Pedagogy in the Malaysian education system, which aims to promote student happiness and character development based on Karamah Insaniah (human dignity). Using a qualitative approach with a Systematic Literature Review (SLR), the research identifies key challenges, including limited teaching resources, insufficient teacher training, diverse student backgrounds, and the influence of societal norms and technology that often conflict with sakinah values. Teachers’ lack of proficiency in fostering harmonious and value-driven learning environments further complicates implementation. The study recommends tailored professional development programs to enhance teachers' skills and understanding of Sakinah Pedagogy, integration of moral and spiritual values across all subjects, and learner-centered approaches that engage students meaningfully. Collaboration among educators, parents, and communities is deemed essential to creating a holistic educational environment that aligns with the principles of sakinah, ensuring that students develop both academically and morally in a balanced and meaningful way.